Digital distraction and academic identity in adolescents: A systematic review of short-form social media use - Ghitsna Nadila Farha; Fattah Hanurawan; Imanuel Hitipew (Cognicia, 2026)
The rapid growth of short-form social media platforms has intensified concerns regarding digital distraction and its implications for adolescents’ academic experiences. This systematic review aims to synthesize empirical evidence on the relationship between digital distraction associated with short-form social media use and academic identity among adolescents. Academic identity is conceptualized as adolescents’ self-perception, commitment, and sense of belonging related to academic roles and learning activities. Following PRISMA guidelines, a systematic search was conducted across multiple academic databases to identify peer-reviewed journal articles published between 2020 and 2024. Eleven studies met the inclusion criteria and were included in the final synthesis. The reviewed studies employed cross-sectional, experimental, and mixed-method designs, with samples consisting primarily of adolescents and secondaryschool students. Quality appraisal was conducted using the Joanna Briggs Institute (JBI) critical appraisal tools. The findings indicate that digital distraction, particularly in the context of intensive short-form social media engagement, is consistently associated with reduced academic focus, fragmented attention, and weakened academic identity. Adolescents who reported higher levels of distraction exhibitedlower academic self-concept, reduced motivation, and diminished engagement with academic tasks. While some studies explicitly examined TikTok use, others addressed short-form or social media use more broadly, suggesting that the observed effects reflect platform-amplified rather than platform-exclusive mechanisms. Protective factors, including strong academic identity, self-regulation skills, and supportiveeducational environments, were found to mitigate the negative academic consequences of digital distraction. Emotional responses related to perceived academic loss, conceptualized as academic grief, emerged as secondary outcomes when prolonged distraction contributed to disengagement and perceived academic failure. Overall, this review highlights academic identity as a central psychological construct linking digital distraction to adolescents’ academic functioning. The findings underscore the need for future longitudinal research to clarify developmental pathways and for educational interventions that strengthen academic identity and digital self-regulation in digitally saturated learning environments.